Women with HIV transitioning through menopause: Insights from the Swiss HIV Cohort Study (SHCS). Issue 4 (22nd February 2022) - Hachfeld, Anna; Atkinson, Andrew; Stute, Petra; Calmy, Alexandra; Tarr, Philip E.; Darling, Katharine; Babouee Flury, Baharak; Polli, Christian; Sultan‐Beyer, Leila; Abela, Irene A.; Aebi‐Popp, Karoline; ,
Abstract: Objectives: We aimed to assess prevalence and age at menopause, identify factors associated with early menopause and explore the provision and utilization of healthcare in women living with HIV in Switzerland. Methods: This was a retrospective Swiss HIV Cohort Study analysis from January 2010 to December 2018. Descriptive statistics to characterise the population and menopause onset. Logistic regression analysis to identify risk factors for early menopause. Results: Of all women in the SHCS, the proportion of postmenopausal women tripled from 11.5% ( n = 274) in 2010 to 36.1% ( n = 961) in 2018. The median age at menopause was 50 years. Early menopause (< 45 years) occurred in 115 (10.2%) women and premature ovarian insufficiency (POI) (< 40 years) in 23 (2%) women. Early menopause was associated with black ethnicity (52.2% vs. 21.6%, p < 0.001), but not with HIV acquisition mode, CDC stage, viral suppression, CD4 cell count, hepatitis C, smoking or active drug use. While 92% of the postmenopausal women underwent a gynaecological examination during the 36 months before menopause documentation, only 27% received a bone mineral density measurement within 36 months after the last bleed and 11% were on hormone replacement therapy at the time of menopause documentation. Conclusions: The median age of women living with HIV at menopause is around 2 years lower than that reported for HIV‐negative women in Switzerland. HIV care providers need to adapt their services to the requirements of the increasing number of women living with HIV transitioning through menopause. They should be able to recognize menopause‐associated symptoms and improve access to bone mineral density measurement as well as hormone replacement therapy.